Climate dynamics and collapse at the end of the Roman Empire - Martín Casado, Juan Manuel (My University, 2022)
In the last few years, the study of extreme environmental phenomena has been gaining protagonism in historical research, as triggering forces of disasters and catastrophes are being valued as a useful tool for historical analysis, creating a denominated “history of disasters”. The capacity of potentially catastrophic natural phenomena, such as earthquakes, or tsunamis, but especially climatic fluctuations, to contribute to the knowledge of political and cultural processes in ancient societies has already been emphasised. This line of work has also contributed to the development of several theoretical and methodological paradigms. Especially the interdisciplinary component, which reflects approaches and a narrative based on a broad group of geological, climatic, archaeological, and literary indicators or “natural archives”. Our case study would be to test the validity of including climate change among the explanatory causes of the crisis of the Roman Empire, more specifically in its western part. We consider it appropriate to approach the recent updating of the explanatory hypothesis that points to a causal link between environmental fluctuations and the historical process of disruption and crisis of the Roman imperial edifice. As specific subject of study, I consider the historical process of the Roman province of Baetica during the Late Antiquity chronological horizon, between the 3rd and 5th centuries AD. This province offers a very interesting scenario as there seems to be a concentration of extreme natural phenomena. Research in coastal environments is beginning to point to the occurrence of a horizon of destruction associated with a high-energy marine event, while inland there is significant evidence of seismic episodes, to the point that there is even talk of a Late Roman “seismic crisis”.
Keywords: Catástrofes naturales - Historia; Clima - Cambios - Historia; Cross-cultural studies; Extreme climate events; Collapse; Roman Empire; Late Antiquity